Renal Sodium- and Potassium-Activated Adenosine Triphosphatase and Sodium Reabsorption in the Hypothyroid Rat - Katz, Adrian I.; Lindheimer, Marshall D. (The Journal of Clinical Investigation, 1973)
The relationship between net tubular reabsorption of sodium and renal microsomal sodium- and potassium-activated adenosine triphosphatase (Na-K-ATPase) was evaluated in hypothyroid and hyperthyroid rats and in age-matched euthyroid controls. Tubular sodium reabsorption per gram of kidney was lower in thyroidectomized rats than in controls (186±14 vs. 246±12 μeq/min; P < 0.005) and was accompanied by a quantitatively similar reduction in Na-K-ATPase specific activity (49.4±2.4 vs. 65.8±2.3 μmol inorganic phosphate (Pt)/mg protein per h; P < 0.001). This decrement was present in both cortex and outer medulla, and was limited to Na-K-ATPase since other representative enzymes not involved in sodium transport (magnesium-dependent adenosine triphosphatase [Mg-ATPase], glucose-6-phosphatase, 5′-nucleotidase) remained unchanged or increased in the hypothyroid animals. Conversely, Na-K-ATPase rose when sodium reabsorption increased in euthyroid rats treated with triiodothyronine. Subsequent experiments were performed to determine to what extent the decrease in Na-K-ATPase is due to lack of thyroid hormone per se or to an adaptive response to decreased reabsorptive sodium load. Triiodothyronine in concentrations of 10-12 to 10-5 M had no effect in vitro on microsomal Na-K-ATPase of either thyroidectomized or euthyroid rats. When hypothyroid rats were uninephrectomized or treated with methylprednisolone, sodium reabsorption per gram kidney increased markedly and was similar to that of intact controls. Despite persistence of the hypothyroid state, Na-K-ATPase specific activity also increased to levels not significantly different from euthyroid animals. These data suggest that decreased tubular sodium transport is a major determinant of the reduction in renal Na-K-ATPase in thyroid deficiency since the latter can be reversed by increasing sodium reabsorption during continuing hypothyroidism. Furthermore, the modest sodium leak of hypothyroid animals does not appear to be due to decreased Na-K-ATPase since it was not corrected by uninephrectomy despite restoration of both cortical and medullary Na-K-ATPase activity to normal by this maneuver. The close correlation between net sodium reabsorption and Na-K-ATPase in all the experimental situations described here demonstrates that renal Na-K-ATPase changes adaptively in hyper- or hypothyroidism as it does in numerous situations in the normal animal, in accord with its postulated role in the active transport of sodium across the renal tubule. Images